Comparison of data hiding using LSB and DCT for image - Ahmed, Zamzam Hohamed (2014)
Steganography is the art and science of hiding information by embedding data into cover media. There are two main domains namely spatial and frequency domain. In this project, a comparison is made between hiding in spatial domain using LSB technique and hiding in frequency domain using DCT technique. Various BMP cover images with 256x256 and 512x512 resolutions for LSB and DCT techniques are used in the experimentations. For DCT technique, various BMP image is converted to JPEG image. Then data is hidden into the JPEG cover image using DCT technique. After that, the JPEG stego image is converted back to BMP stego image. These BMP stego images from LSB and DCT are compared using PSNR. Results from these experiments show that 75% of the stego images hidden using LSB has shown higher PSNR values than stego images hidden using DCT. This means that the stego image hidden using LSB has shown a much closer similarity to the cover image than stego image hidden using DCT, thus much harder to detect hidden data in the stego image by LSB.